Databases and Associated Bioinformatic Tools in Studies of Food Allergens, Epitopes and Haptens – a Review - Bucholska Justyna; Minkiewicz Piotr; Darewicz Małgorzata; Iwaniak Anna (Polish Journal of Food and Nutrition Sciences)
Allergies and/or food intolerances are a growing problem of the modern world. Diffi culties associated with the correct diagnosis of food allergies result in the need to classify the factors causing allergies and allergens themselves. Therefore, internet databases and other bioinformatic tools play a special role in deepening knowledge of biologically-important compounds. Internet repositories, as a source of information on different chemical compounds, including those related to allergy and intolerance, are increasingly being used by scientists. Bioinformatic methods play a signifi cant role in biological and medical sciences, and their importance in food science is increasing. This study aimed at presenting selected databases and tools of bioinformatic analysis useful in research on food allergies, allergens (11 databases), epitopes (7 databases), and haptens (2 databases). It also presents examples of the application of computer methods in studies related to allergies.